2023
DOI: 10.3390/molecules28041541
|View full text |Cite
|
Sign up to set email alerts
|

Effective Removal of Sulfonamides Using Recyclable MXene-Decorated Bismuth Ferrite Nanocomposites Prepared via Hydrothermal Method

Abstract: Developing a simple and efficient method for removing organic micropollutants from aqueous systems is crucial. The present study describes the preparation and application, for the first time, of novel MXene-decorated bismuth ferrite nanocomposites (BiFeO3/MXene) for the removal of six sulfonamides including sulfadiazine (SDZ), sulfathiazole (STZ), sulfamerazine (SMZ), sulfamethazine (SMTZ), sulfamethoxazole (SMXZ) and sulfisoxazole (SXZ). The properties of BiFeO3/MXene are enhanced by the presence of BiFeO3 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Ti 3 C 2 MXene has been synthesized by etching the MAX phase with hydrofluoric acid (HF) according to previous work. 19 5.0 g of MAX phase was immersed in 80 mL HF solution (40%), and the Al layer was peeled off by stirring for 24 hours at room temperature. The obtained product underwent multiple washes with distilled water until the pH approached 7.…”
Section: Synthesis Of Ti 3 C 2 Mxenementioning
confidence: 99%
See 1 more Smart Citation
“…Ti 3 C 2 MXene has been synthesized by etching the MAX phase with hydrofluoric acid (HF) according to previous work. 19 5.0 g of MAX phase was immersed in 80 mL HF solution (40%), and the Al layer was peeled off by stirring for 24 hours at room temperature. The obtained product underwent multiple washes with distilled water until the pH approached 7.…”
Section: Synthesis Of Ti 3 C 2 Mxenementioning
confidence: 99%
“…The addition of BiFeO 3 nanoparticles to MXene improves their properties by increasing the available surface area for efficient sulfonamide removal. 19 Yan et al synthesized Nb 2 CT x MXene nanosheets and used them as an adsorbent for dyes. Their results revealed that the synthesized adsorbent exhibits excellent absorption capability for both cationic and anionic dyes, with a maximum adsorption capacity beyond 500 mg g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the scientific significance of BiFeO 3 is firmly rooted in the relentless pursuit of advancing our comprehension of these multifunctional nanoparticles and harnessing their capabilities for theoretical and practical advancements in numerous research arenas [15,16]. The synthesis of BiFeO 3 nanoparticles encompasses an array of techniques, including solid-state reactions [17], coprecipitation [18], the wet chemical route [19], microemulsion technique [20], the hydrothermal route [21], the sol-gel process [22], the auto-combustion route [23], sono-synthesis [24], the Pechini method [25], microwave methods [26], and others [27]. These techniques have been meticulously scrutinized and enhanced to produce BiFeO 3 nanostructures with tailored properties suited for diverse applications.…”
Section: Introductionmentioning
confidence: 99%